Studies into iridium-catalysed asymmetric allylic alkylation towards the total synthesis of a dolabellane - Jiang, L (2016)
In recent years, iridium-catalysed asymmetric allylic substitution has received considerable attention because it is a valuable tool to selectively synthesise chiral compounds with high ee from simple starting materials. This thesis presents an efficient catalytic system for the decarboxylative iridium-catalysed asymmetric allylic alkylation (AAA) in which a wide range of allylic β-ketoester substrates was converted into chiral ketones in good yields with high regio- and enantioselectivities. A possible mechanism for decarboxylative iridium-catalysed AAA is also proposed in this thesis.